DEVELOPING FUN THINKERS BOOK LEARNING MEDIA ON THE TOPIC OF PERISTIWA ALAM YANG TERJADI DI INDONESIA AT GRADE V OF ELEMENTARY SCHOOL - Mariatul Kibtiah; Nana Hendracipta; Encep Andriana (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This research aimed to develop fun thinkers book learning media on the topic of “Peristiwa alam yang terjadi di Indonesia” for grade V elementary school students and to determine the feasibility of the learning media. This research was research and development involving six steps: (1) problem analysis, (2) data information collection, (3) product design, (4) design validation, (5) product revision, and (6) product testing. The subjects in this study were 10 grade V students. The data were collected through interviews, questionnaires, and validity assessments from material experts, language experts, media experts, as well as a questionnaire of students’ responses. The result of this research was a fun thinkers book learning media consisting of two components: a book and a frame. The feasibility of the media was obtained from the assessments of the experts, namely media experts, material experts, language experts, and students’ responses, with average percentages of 90.8%, 97.5%, 81.82%, and 82.23%, respectively. Based on these results, it was concluded that the fun thinkers book learning media was feasible to be used as a learning media on the topic of “Peristiwa alam yang terjadi di Indonesia.”